2001
DOI: 10.1212/wnl.56.6.781
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evidence of widespread morphological variations of the brain in dyslexia

Abstract: The MR images of 16 men with dyslexia and 14 control subjects were compared using a voxel-based analysis. Evidence of decreases in gray matter in dyslexic subjects, most notably in the left temporal lobe and bilaterally in the temporoparietooccipital juncture, but also in the frontal lobe, caudate, thalamus, and cerebellum, was found. Widely distributed morphologic differences affecting several brain regions may contribute to the deficits associated with dyslexia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

19
142
6
8

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(175 citation statements)
references
References 9 publications
19
142
6
8
Order By: Relevance
“…Differences in non-cortical regions included the hippocampus/parahippocampus, amygdala, globus pallidus and putamen. These brain regions correlate with areas identified previously as being involved in reading and/or symbol decoding either structurally or functionally (Kronbichler et al 2007;Brambati et al 2006;Cao et al 2006;Casanova et al 2005;Silani et al 2005;Vinckenbosch et al 2005;Aylward et al 2003;Eckert et al 2003;Ruff et al 2003;Brown et al 2001;Eliez et al 2000;Rumsey et al 1999). …”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Differences in non-cortical regions included the hippocampus/parahippocampus, amygdala, globus pallidus and putamen. These brain regions correlate with areas identified previously as being involved in reading and/or symbol decoding either structurally or functionally (Kronbichler et al 2007;Brambati et al 2006;Cao et al 2006;Casanova et al 2005;Silani et al 2005;Vinckenbosch et al 2005;Aylward et al 2003;Eckert et al 2003;Ruff et al 2003;Brown et al 2001;Eliez et al 2000;Rumsey et al 1999). …”
Section: Discussionsupporting
confidence: 73%
“…Compared to structural imaging studies before 2005 (Brambati et al 2004;Eckert et al 2003;Brown et al 2001;Eliez et al 2000), several recent studies, using more optimized and contemporary imaging techniques, have reported mixed patterns of increased and decreased gray matter volumes in dyslexia. More specifically, these studies show increases in GM volume in several cortical areas pertaining to language including: posterior, medial and inferior temporal gyri, precentral and postcentral gyri, superior and medial frontal gyri and precuneus (Kronbichler et al 2007;Silani et al 2005;Vinckenbosch et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the anterior superior cortex includes Broca's area. Decreased gray matter density was found in the left temporal lobe involving superior (above T3), middle (T3), inferior (below T3), and mesial (no surface representation) structures in dyslexics (Brown et al, 2001). Studies on the corpus callosum have found variable and inconsistent abnormalities.…”
mentioning
confidence: 97%
“…Voxel-based morphometry reveals differences in gray-matter volume indices in individuals with DD (compared with typical reading controls) in various areas of the brain, including left occipitotemporal and temporoparietal areas (44,(56)(57)(58)(59)(60)(61), bilateral fusiform (59), and lingual gyrus (LG) (58) as well as the cerebellum (56-58). Morphological abnormalities in these regions can be identified even before reading skills are present in children as young as 5 to 6 y of age, suggesting atypical early development or even a genetic basis for DD (62).…”
mentioning
confidence: 99%